O uso do gênero caso para o ensino no âmbito do estágio supervisionado em letras: discussões sobre a relação teoria e prática. - Araujo, Mirelle da Silva Monteiro (2016)
This master‟s thesis is linked to the field of Applied Linguistics and its general objective is to contribute to the debate on the relationship between theory and practice within the scope of the degree in Letters (Portuguese Language) by using the textual genre case for teaching. And, in particular, to identify the theoretical discourses mobilized by students in solving a problem situation approached in the case for teaching and analyze how teachers in initial training project themselves on teacher‟s role in the solution of a problem situation. For that, we used the Supervised Internship notions by Pimenta (2005, 2006); Pimenta and Lima (2010); Sousa, Lucena and Segabinazi (2014); Tardif (2011); Ludke (2013) and Nóvoa (1992); the understanding of teaching knowledge by Tardif (2000, 2011) and also the theoretical basis on case for teaching by Roesch and Fernandes (2007); Gil (2004); Gomes (2006) and Fachin, Tanure and Duarte (2007) and also the notion of enunciative responsability of Adam (2008). The proposal for using the case for teaching in this research takes this genre based on Swales‟ theory (2009) and the regularities for the characterization of the genre by Paré and Smart (2003). We have conducted an interventionist research in the context of Supervised Internship I of the Bachelor of Arts course in Portuguese Language at Federal University of Paraíba. We have applied two cases for teaching in two groups of Supervised Internship I, which amounted to forty collaborators. The corpus of this research consisted of written responses provided by the groups to the questions of the two cases for teaching. We defend the assertion that the case for teaching enables teachers in initial training to discuss actual aspects of the teaching career, showing the relationship between theory and practice in it. The analysis of the answers provided by our collaborators showed that the case for teaching enables them to: a) Visualize theoretical aspects in the practice of teacher inserted in the workplace and in their teaching materials; b) Relate theory with teacher training inserted in school; c) Relate theories to official documents; d) Project themselves in the image of teachers and make decisions motivated by the theory; e) Think of a student learning from the theoretical conceptions and f) Defend that the decisions of a teacher, on the problems of teaching practice, should not always be consistent with their theoretical perspectives.